Percepção do usuário sobre o acesso a medicamentos nos equipamentos municipais do SUS de Álvares Machado-SP - Marcondes, Flávia Fernanda Catussi (Universidade Federal de São Carlos, 2024)
The availability and rational use of medicines are crucial aspects to guarantee comprehensive healthcare in the Unified Health System (SUS), being directly linked to the sufficiency in terms of availability, quantity and quality of medicines provided. Among other issues, understanding people's access to medicines in the health system is fundamental for effective management, which seeks comprehensiveness and resolution in the care provided. To contribute in this sense, the perceptions of users of Pharmaceutical Assistance in Álvares Machado, SP, in relation to access to medicines provided by the local SUS were explored. Through a clinical-qualitative approach, using individual interviews and thematic content analysis, instability in the supply of medicines and difficulties in accessibility to the central pharmacy were identified as problems that hinder the effectiveness, efficiency and effectiveness of the desired health care. by SUS. The relationship established between the pharmaceutical team and users, as well as the organization of the flow for access to medicines, were positive points observed in Pharmaceutical Assistance. The decentralization and peripheralization of PHC to the PHC territory and the establishment of a strategic management model capable of ensuring regularity in the supply of medicines were proposed. One of the suggested strategies is the creation of protocols and guidelines guided by lines of care.

La disponibilidad y el uso racional de los medicamentos son aspectos cruciales para garantizar la integralidad de la atención de salud en el Sistema Único de Salud (SUS), siendo diretamente vinculado a la suficiencia en términos de disponibilidad, cantidad y calidad de los medicamentos proporcionó. Entre otras cuestiones, comprender el acceso de las personas a los medicamentos en el sistema de salud es fundamental para una gestión eficaz, que busque la integralidad y resolución en la atención brindada. Para contribuir en este sentido, el percepciones de los usuarios de la Asistencia Farmacéutica en Álvares Machado, SP, en relación acceso a medicamentos proporcionados por el SUS local. A través de un enfoque clínico-cualitativo, mediante entrevistas individuales y análisis de contenido temático, inestabilidad en el suministro de medicamentos y dificultades em accesibilidad a la farmacia central como problemas que socavan la eficacia, la eficiencia y efectividad de la atención de salud deseada por el SUS. La relación que se establece entre el equipo empresa farmacéutica y usuarios, así como la organización del flujo de acceso a medicamentos, fueron puntos positivos observados en la Asistencia Farmacéutica. Ellos eran propuestas para la descentralización y periferización de la FA hacia el territorio de la APS y el establecimiento de un modelo de gestión estratégica capaz de garantizar la regularidad em suministro de medicamentos, una de las estrategias sugeridas es la creación de protocolos y lineamientos guiados por líneas de atención.
User perception about access to medicines in municipal SUS equipment in Álvares Machado-SP
Percepción de los usuarios sobre el acceso a medicamentos en los equipos municipales del SUS en Álvares Machado-SP
Keywords: Assistência farmacêutica; Acesso a medicamentos; Uso racional de medicamentos; Atenção primária a saúde; Sistema único de saúde; Pharmaceutical care; Access to medicines; Rational use of medicines; Primary health care; Health unic system; Cuidado farmacéutico; Sistema único de Salud; CIENCIAS DA SAUDE::FARMACIA; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS DA SAUDE::FARMACIA::ANALISE E CONTROLE E MEDICAMENTOS; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA